EMPATHY AS A FACTOR IN PHYSICIANS’ EFFECTIVENESS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article explores the pivotal role of empathy in enhancing physicians' effectiveness within clinical practice. Through a systematic review of empirical studies, it examines how empathy influences various aspects of patient care, including satisfaction, adherence to treatment, anxiety reduction, diagnostic accuracy, and overall clinical outcomes.